SURGICAL INCISION TECHNIQUE APPROACH ON DISTAL FEMUR FRACTURE A LITERATURE REVIEW - Rudiansyah Harahap (Journal Medical Universitas muhammadiyah Makassar, 2021)
Distal Femur fractures are rare, with the literature reporting a prevalence of 0.5% of all fractures1. Incidence rates of distal femur fractures have only been reported in a small number of studies2,3. Fractures of the distal femur is described as a classic fragility fracture, with the mean age of patients reported as 67.3 years and the vast majority of fractures (83%) occurring in women1,4.A study shows an incidence of distal femur fractures is 8.7/100,000/year. After the age of 60 years, a rapid increase in the incidence of distal femoral fractures was observed for both genderswith a considerable female predominance5. Nowdays, the surgical management of distal femur fracture is evolving. This review will discuss about the incision approach on distal femur approaches.